Pengaruh Intensitas Kebisingan dan Penggunaan Alat Pelindung Diri (APD) Terhadap Daya Dengar Pekerja Di Bagian Produksi PT Master Wovenindo Label - Marsanudin Lulang; Revie Fitria Nasution (STIKes Persada Husada Indonesia, 2017)
Noise is one of the physical factor that can lead to decrease of hearing power. This can be prevented and minimized by using of Personal Protective Equipment (PPE) during work. The purpose of this study to determine the effect of the use of PPE on the hearing of the workers in the production of PT Master Wovenindo Label. Research design used quantitative analytic with csoss sectional approach. Retrieval sampling techniques method used purposive sampling with a sample of 80 respondents. Analysis of data using statistical test chi-square with a significant level α = 0,05 using SPSS. The results showed that there is a significant influence between the use of personal protective equipment to the hearing power (p<0,05) in the production section PT Master Wovenindo Label.